(untitled) (Architecture Image Studies, 2020)
The present research explores the use of the art practices in “no-places” as an instrument of urban regeneration. “No-places” are meant as architectural and urban spaces where people perceive to be in a decayed and anonymous areas, without identity and ties with the territory due to their shapes and their ways of fruition. The goal is to transform them into ‘new places’, creating a different relationship between people and spaces. This is achieved without structural and architectural measures, but modifying those aspects concerning the perception, orientation and recognition to have an impact on the fruition and on the sense of belonging to the place. In particular, research focuses on the anamorphic artistic installations; anamorphosis is a geometrical process of optical illusion based on a distorted projection that enables the recognition of the original image watching it from a specific point of view. The enigmatic and fragmented labyrinth of signs becomes understandable for the observer only when he recomposed it with his eyes and his movement, thereby contributing to define new perception and use of the space. In the first part of the text we analyze some installations that use the anamorphosis as a tool of urban acupuncture; in the second part, the Boscoreale railway station constitutes the case study for the application of anamorphosis to a “no-place” of the urban mobility.